The Triglyceride-Glucose Index: A Potential Simple Screening Tool for Insulin Resistance in Young Adults - Kenny; Efrida; Elfira Yusri; Rismawati Yaswir; Husni; Syofiati (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: Insulin resistance is a key factor in the development of metabolic diseases, which are increasingly prevalent in young adults. Early detection is crucial for timely intervention. The triglyceride-glucose (TyG) index, calculated from fasting triglyceride and glucose levels, has emerged as a potential alternative to the more complex homeostasis model assessment of insulin resistance (HOMA-IR). This study aimed to evaluate the agreement between the TyG index and HOMA-IR in detecting insulin resistance in young adults. Methods: A cross-sectional study was conducted on 102 non-diabetic young adults (aged 18-22 years). Fasting blood samples were collected to measure triglyceride, glucose, and insulin levels. The agreement between the TyG index and HOMA-IR was assessed using the Kappa coefficient. Results: The median age of the participants was 20 years, with 65.7% being female. The prevalence of insulin resistance was 79.4% based on the TyG index (cut-off value of 4.25) and 43.1% based on HOMA-IR (cut-off value of 2.2). The agreement between the two indices was slight (Kappa = 0.155, p = 0.001). Conclusion: The TyG index showed a higher prevalence of insulin resistance compared to HOMA-IR in this population. However, the agreement between the two indices was low. Further research is needed to validate the TyG index as a screening tool for insulin resistance in young adults.